2016
DOI: 10.3390/dj4040044
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Poor Oral Health: A Comparison of Postmenopausal Women

Abstract: Inter-relationships between traditional dental variables are becoming more evident in far reaching aspects of life, such as psychosocial interaction, self-esteem, overall health and even occupational performance. This study compares quality of life (QoL) in postmenopausal women (PMW) with poor oral health (POH) with QoL in PMW with good oral health. A total of 200 randomly recruited PMW received a dental evaluation and completed the Utian Quality of Life Survey. The participants were divided into POH and healt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…They demonstrated that, compared to the scores obtained in the healthy control group, the sexual test scores were lower in each study group with abnormal scores of PPD, CAL, and PI, all of which were the parameters used in diagnosing periodontitis (DeBaz et al, 2015). In another survey study published in 2016, it was reported that postmenopausal women with poor oral health had significantly low sexual test scores (Williams et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…They demonstrated that, compared to the scores obtained in the healthy control group, the sexual test scores were lower in each study group with abnormal scores of PPD, CAL, and PI, all of which were the parameters used in diagnosing periodontitis (DeBaz et al, 2015). In another survey study published in 2016, it was reported that postmenopausal women with poor oral health had significantly low sexual test scores (Williams et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…However, those studies provided limited information about the severity and clinical subtypes of sexual dysfunction (DeBaz et al, 2015;Williams et al, 2016). They investigated the quality of sexual life in women with periodontitis by using only the three respective items of the general quality of life scale (Utian et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…5 The research of Williams et al showed that postmenopausal people with poor oral health had significantly poorer quality of life. 6 The results of Debaz et al showed that patients with periodontitis had a poor quality of life than healthy subjects, with significant physical, social and psychological impacts. 7 In conclusion, a relationship between menopausal women with periodontitis affects patients' quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…3,5 Oral health problems cannot only be seen as dental problems, but they should be viewed as a whole; [6][7][8] they affect mortality, overall health, digestion, speech, social mobility, employment, selfesteem, quality of life, and well-being. 3,9 Chile's public oral health policy "is geared towards the prevention and promotion of oral health of the population, especially on the most vulnerable, and it considers recovery activities in prioritized groups through cost-effective actions based on the most available evidence". The demand for care is very high because of the extent of damage to the population and scarce dentist hours, so the State is in need of prioritizing specific age groups, in order to have a long-term health impact.…”
Section: Introductionmentioning
confidence: 99%